Managerial competence, credit policy and financial performance of co mmercial banks in Uganda - Kyomuhangi, Diana Susan (Kampala, 2015)
Unpublished dissertation (Msc. ACC. & FIN.) - Makerere University, 2 015
Includes bibliographical references (p. 47-53).
Keywords: Banks and banking -- Uganda; Bank management -- Uganda